Flexão e estabilidade de barras usando o modelo de Bickford-Reddy: uma abordagem pelo método dos elementos de contorno - Maia, Cibelle Dias de Carvalho Dantas (2016)
In this work, new solutions based on the Boundary Element Method (BEM) are established for the linear analysis of bending and stability problems of Reddy-Bickford beams. All mathematical steps to write the BEM representation are properly presented: transformation of governing differential equations into equivalent integral equations, deduction of fundamental solutions, formation and solution of algebraic representation.In addition, elastic foundations (winkler and pasternak’s types) attached to Reddy-Bickford beams are solved by BEM as well. It is also addressed a convenient strategy for discontinuities in the area such as abrupt change in geometry of the cross section (stepped beam), intermediate axial load, intermediate supports (continuous beam). Numerical examples incorporating various types of discontinuities and boundary conditions in the field are presented to validate the solutions proposed BEM.